Sistem Pendukung Keputusan Penentuan Dalam Penentuan Mutu Beras Miskin Menggunakan Fuzzy MADM Model Yager: Decision Support System in Determining The Quality of Poor Rice using Fuzzy MADM Model Yager - Rini Meiyanti (Fakultas Ilmu Komputer Universitas Almuslim Bireuen - Aceh, 2021)
Rice distribution for economically disadvantaged group of people is one of the main operational activities of Bulog Company to advance Indonesian society welfare. Decision making for rice quality for the addressee often became a complicated problem. Overcoming those problems takes an effective step in order to take a decision. One way to do so is to perform the classification process and search for the best result using the existing data. The use of software can be an optimal solution of the problem by using the method of Fuzzy Multi Attribute Decision Making (FMADM) Yager. This application will ease Perum Bulog to determine the best rice quality to be distributed to the economically disadvantaged group of people. After fuzzification of data to work with FMADM Yager perform pairwise comparisons are based on the value of an attribute of interest, determined the value of the weight (W), reappointment, and ranking the final results. Based on the results, then the KP. Adi Rizka an optimal alternative to the value of 0.8131 which it included in the category of suitable is 0.8. The system is built using the PHP programming language and MySQL database.